Differences In The Description Of Gestation Age Of Premature Babies Towards Body Increase In Nesting Implementationin RSUD. DR. SOEDIRMAN Kebumen - Wuri Utami; Ning Iswati; Sri Abdi Lestari (INVOLUSI: Jurnal Ilmu Kebidanan, 2021)
Background: Premature babies with gestational age less than 37 weeks are born with organ immaturity that affects adaptation difficulties in extra-uterine life and is at risk of morbidity and mortality due to low birth weight. To support the ability of premature babies to adapt to their weaknesses, it is necessary to apply nesting to support infant development, facilitate the development of premature babies in the form of physiological and neurological conditions. experimental method with a comparative approach. Respondents in this study were 38 premature babies who were taken using accidental sampling. Data were collected using an observation sheet. Data analysis used chi square statistical test. Results: Based on the results of the study, most of the frequency of gestational age aged 29-34 weeks was 26 respondents (68.4%). %). And most of the frequency of baby body weight after the implementation of nesting mostly weighing less than 1500 grams as many as 23 respondents (60.5%). The results of the chi square analysis can be seen that the p value is 0.588. Conclusion: There is no significant difference in the picture of gestational age of premature babies to weight gain in the application of nesting in RSUD Dr. Sudirman Kebumen. Recommendation: It is hoped that the next researchers will be able to investigate the application of nesting with an equivalent gestational age.